Fikih Bekerja - Fachri Fachrudin (Institut Agama Islam Sahid Bogor, 2020)
Islam is not a religion that only has a vertical dimension between a servant and his Lord, it is a way of life that regulates all aspects of human life, including the relationship between a human being and another human being. Including Islam regulates how a human being maintains the existence of his life in the world. One of the main goals of Islam is hifdz al-mal, which is to protect property, which is the right of every human being. From here Islam gives freedom for humans to seek wealth as a tool to fulfill their lives. Islam gives a very high appreciation in work. The basic principle in Islam is to do a job that is valuable and useful, and vice versa, work that is useless and brings harm is declared as a forbidden job and even considered an ally of Satan. This can also be seen in the many verses of the Qur'an and Hadith that call on a Muslim to work.The verse of the Qur'an that regulates ethics in work is the word of Allah ta'ala in QS. Al-Anfaal: 27